Legal View of Employment on Omnibus Law Policy in 2020 - Yudha Ginanjar (IHSA Institute, 2021)
Indonesia is a country that really cares and upholds the dignity of its people, for that the government through its laws explicitly and sovereignly regulates the sector of the national labor system. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that, in general, the rights and obligations of workers are a responsibility that is directly protected by law and Pancasila, because juridically the birth of labor law in Indonesia is the result of thinking to strive for an empowerment for workers in demanding all rights and social justice, in addition to the purpose of holding protection for workers as well, as a tangible manifestation of the government in the face of an increasingly global work system in various sectors, for this reason the guarantee and safety of workers is very important. attempted by various groups, apart from laws, legal policies for workers are also contained in a government regulation of the republic of Indonesia number 31 of 2006 and the national job training system, the decree of the minister of manpower of the republic of Indonesia in 2004, and the 2007 regulation of the minister of manpower and transmigration on the procedures for setting Indonesian national work competency standards.